The Effect of Ownership Structure on Corporate Social Responsibility Moderated Financial Performance of Food & Beverage Industry in Indonesia - Dyah Agustina; Henny Setyo Lestari (International Journal of Education, Information Technology, and Others, 2022)
This study aims to analyze the effect of ownership structure includes institutional ownership and managerial ownership on corporate social responsibility. The study also examines the effect of financial performance on the relationship between ownership structure and CSR. The data used in this study is secondary data sourced from the annual reports of food & beverage industry listed on the Indonesia Stock Exchange (IDX) during the 2017-2021. The research sample was selected using purposive sampling method in order to obtain 29 companies as samples. The data analysis used to test the hypothesis is multiple regression analysis using the Eviews 12 software. The results show that institutional ownership and managerial ownership have a negative and significant effect on CSR. The financial performance variable measured by ROA has a negative and significant effect on moderating the relationship between institutional ownership and CSR, but the measurement with Tobins'Q has no effect on moderating the relationship. Meanwhile, financial performance measured by ROA and Tobins'Q has no effect in moderating the relationship between managerial ownership and CSR. The findings have practical implications for managers, regulators, and investor for improving CSR. Future research is expected to be able to examine the effect other ownership structures on CSR and using sample of various sectors companies